Salinomycin inhibits the tumor growth of glioma stem cells by selectively suppressing glioma-initiating cells - CHEN, TUNAN (Mol Med Rep, 2015)
Glioma-initiating cells are a small population of cells that have the ability to undergo self-renewal and initiate tumorigenesis. In the present study, the potential role of salinomycin, a polyether antibiotic, on the suppression of glioma cell growth was investigated. GL261 glioma cells were maintained in a stem-cell-like status [GL261 neurospheres (GL261-NS)] or induced for differentiation [GL261 adherent cells (GL261-AC)]. It was demonstrated that salinomycin significantly reduced the cell viability of GL261-NS and GL261-AC cells in a dose-dependent manner, with a more substantial inhibition of GL261-NS proliferation (P<0.05). The inhibitory effect of salinomycin on cell growth was more effective than that of 1-(4-amino-2-methyl-5-pyrimid l)-methyl-3-(2-chloroethyl)-3-nitrosourea hydrochloride and vincristine (P<0.05). Salinomycin depleted GL261-NS from tumorspheres and induced cell apoptosis. In addition, salinomycin prolonged the median survival time of glioma-bearing mice (P<0.05). Therefore, the present study indicated that salinomycin may preferentially inhibit glioma-initiated cell growth by inducing apoptosis, suggesting that salinomycin may provide a valuable therapeutic strategy for the treatment of malignant glioma.